The Meanings of Sanskrit Loanwords in Thai and Javanese Languages - Hamam Supriyadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
Through history of nation building, Thai and Javanese people interacted with other language speakers. For example, they interacted with Indian mbrchants who also brought their literature and religions. In their contacts, Thai and Javanese speakers adopted Sanskrit words for enriching their own vocabularies. This article attempts to describe the meanings of Sanskrit loanwords. In comparison between the meanings of Sanskrit loanwords in Thai and Javanese languages, there are 14 categories of semantic adaptations which are found in both languages. These changes reflect the changes of the socio-cultural background of the Thai and Javanese speakers.